HEALTH AND NUTRITIONAL STATUS ASSESSMENT OF ELDERLY AT MADIUN NURSING HOME TOWARD LEADING LONG TERM CARE FACILITIES - Ratu Dien Prima Fermeza; Farapti Farapti; Dianis Wulan Sari; Neisya Pratiwindya Sudarsiwi; Aziz Nashiruddin Habibie; Zaenal Abidin (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2026)
Introduction: The growth of the elderly population poses challenges in managing degenerative diseases, nutritional problems, and functional decline. This study aimed to assess basic health status, nutritional profile, and body composition of older adults as a foundation for long-term care development. Methods: This community service was conducted in an institutional elderly care facility and community setting located in Madiun, East Java. Participants were adults aged ≥60 years, consisting of 51 subjects (12 institutionalized and 39 community-dwelling retirees). Inclusion criteria were older adults willing to participate, while exclusion included acute illness. Data were collected through interviews, observation, anthropometry, vital signs, body composition analysis, and blood glucose measurement. The activities comprised group discussions, direct observations, and health evaluations, complemented by interactive sessions like walking track games designed to assess and improve muscle strength, with health messages placed along the path. Additionally, brain exercise sessions were conducted to enhance motor coordination. Results: The participants were aged 58-88 years, representing an elderly population group. Findings revealed high prevalence of isolated systolic hypertension (35.7%), hyperglycemia (14.6%), overweight/obesity (50%), and low bone mass (88.1%), despite 95.2% having normal muscle mass. Conclusion: Early screening and integrated interventions are essential for detecting abnormalities in blood pressure, glucose, body composition, and osteoporosis risks among older adults, including hypertension, hyperglycemia, overweight/obesity, and low bone mass, in order to promote healthy aging. Pondok Lansia Madiun has the potential to serve as a strengthen community-based long-term care facilities in Indonesia. KEYWORDS body composition; health status; long-term care facilities; nutritional assessment; older adults